ANALYSIS OF FLEXOGRAPHY RASTER ANGLE IN OFFSET PRINTING ABOUT THE âˆ†E OVERPRINT VALUE - Erwandi Widyanata (Politeknik Negeri Media Kreatif, 2021)
Abstract: Some printing technique have distinctive screen angle. Offset printing have certain screenangle, there is Cyan = 15º, Magenta = 45º, Yellow = 0º/90º, and key 75º. While on Flexography printing have different certain with Offset printing. Flexography need deviation 7,5º every angle, becoming Cyan = 22,5º, Magenta = 52,5º, Yellow = 7,5º, and key 82,5º. Special for yellow, screen angle must 0º or 90º because it have lowest contrast value. If set out of 0º or 90, it will be high distortion. Element overprint can help to showingeffect from color distortion because on element oveprint having 2 pile up raster. Significantdistortion can measured and controled. Therefor need researched how effect of applied different screen angle. This research using 20 sample by Flexography angle and 20 sampleby Offset angle were printed using the Offset printing technique and then measured the CIELab value in Blue. Result of this research is the occurrence of significant color deviation due to changes in the raster angle. Keywords: Flexography, Offset, Overprint